Lysine Ethylation by Histone Lysine Methyltransferases. (24th October 2019) - Al Temimi, Abbas H. K.; Martin, Michael; Meng, Qingxi; Lenstra, Danny C.; Qian, Ping; Guo, Hong; Weinhold, Elmar; Mecinović, Jasmin
Abstract: Biomedicinally important histone lysine methyltransferases (KMTs) catalyze the transfer of a methyl group from S ‐adenosylmethionine (AdoMet) cosubstrate to lysine residues in histones and other proteins. Herein, experimental and computational investigations on human KMT‐catalyzed ethylation of histone peptides by using S ‐adenosylethionine (AdoEth) and Se ‐adenosylselenoethionine (AdoSeEth) cosubstrates are reported. MALDI‐TOF MS experiments reveal that, unlike monomethyltransferases SETD7 and SETD8, methyltransferases G9a and G9a‐like protein (GLP) do have the capacity to ethylate lysine residues in histone peptides, and that cosubstrates follow the efficiency trend AdoMet>AdoSeEth>AdoEth. G9a and GLP can also catalyze AdoSeEth‐mediated ethylation of ornithine and produce histone peptides bearing lysine residues with different alkyl groups, such as H3K9meet and H3K9me2et. Molecular dynamics and free energy simulations based on quantum mechanics/molecular mechanics potential supported the experimental findings by providing an insight into the geometry and energetics of the enzymatic methyl/ethyl transfer process. Abstract : Transfer window : Histone lysine methyltransferases, which catalyze the methylation of histones with S ‐adenosylmethionine cosubstrate, have a limited capacity to catalyze ethylation of histones with S ‐adenosylethionine (AdoEth) and Se ‐adenosylselenoethionine (AdoSeEth) cosubstrates. Insights into the geometry and energetics of the enzymatic methyl/ethyl transfer process are reported.